Scripting in Java : integrating with groovy and JavaScript - Sharan, Kishori (Apress, 2014)
Scripting in Java teaches you how to use the Java Scripting API and JavaScript to execute scripts and take advantage of the features of a scripting language while developing Java applications. The book also covers topics that enable scripting languages to take advantage of Java features and the Java class library, including the new Java Collections and JavaFX 8 APIs. Most of the examples in this book use JavaScript on the Nashorn engine. Author Kishori Sharan will show you scripts in JavaScript to demonstrate its power and use in your Java applications. Some of the examples use the jrunscript and jjs command-line tools. Furthermore, debugging is discussed to equip you for situations when or if you encounter any issues with this kind of Java scripting. After reading and using this book, you will have most of what you need to do scripting in Java.